Sustainable energy production and resilience towards floods by using hydro and solar photovoltaic energy (Advances in Civil and Architectural Engineering, 2024)
Unexpected and intense floods have become more frequent recently; this is related to extreme weather events that are difficult to predict accurately. This necessitates new solutions to decrease the risk of flooding urban and rural areas. Moreover, such solutions should have negligible impact on the environment. There are several concepts, tools, and technical measures for preventing floods, one of which is the ‘monkey cheek’ concept for flood protection, used in Thailand for protection from river and sea floods. Monkeys collect food in their mouths and eat subsequently in stages. In a similar manner, excess water from floods could be collected and stored in reservoirs, sags, canals, floodplain forests, and unused space. Collected water could then be used for irrigation. In most cases, collected water must be pumped to distant or higher locations compared to the location where the water was collected. This requires electric energy for the pumps. This paper analyses a case study for the presented concept for the town of Ludbreg in Croatia, currently undergoing real-site measurements and calculations. A rescaled adjusted partial sums method is applied for the analysis. It has been shown that the energy potential of the local, small river Bednja in the observed location could be approximated using the “monkey cheek’’ concept. Within this, using the produced electricity from small hydropower plants and solar photovoltaic systems has been proven promising. The solution avoids building dams for flood protection, satisfying the environmental aspects.